Immunotherapy in allergic fungal sinusitis: The controversy continues. A recent review of literature - Doellman, Mary S. (OceanSide Publications, Inc., 2013)
Allergic fungal sinusitis (AFS), also referred to as allergic fungal rhinosinusitis (AFRS), is a noninvasive, eosinophilic form of recurrent chronic allergic hypertrophic rhinosinusitis. AFS has distinct clinical, histopathological, and prognostic findings that differentiate it from other forms of sinusitis. The core pathogenesis and optimum treatment strategies remain debated. Concerns surround the use of immunotherapy for AFS because allergen-specific immunoglobulin G (IgG) induced by immunotherapy could theoretically incite a Gell and Coombs type III (complex mediated) reaction. Type I hypersensitivity is established by high serum levels of allergen-specific IgE to various fungal antigens and positive Bipolaris skin test results. Type III hypersensitivity is established by an IgG-mediated process defined by the presence of allergen-specific IgG that forms complexes with fungal antigen inducing an immunologic inflammatory response. These reveal the multiple immunologic pathways through which AFS can impact host responses. Recent literature establishing benefits of fungal immunotherapy and no evidence of type III–mediated reactions, severe local reactions, or delayed reactions, indicate that application of AFS desensitization is a reasonable therapeutic strategy for this difficult to manage entity. Our review should encourage further clinical acceptance of AFS desensitization because the existing literature on this subject shows benefits of fungal immunotherapy and no evidence of type III–mediated reactions, severe local reactions, or delayed reactions.